2016
DOI: 10.1016/j.bpj.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Cholesterol Modulates Superwarfarin Toxicity

Abstract: Superwarfarins are modified analogs of warfarin with additional lipophilic aromatic rings, up to 100-fold greater potency, and longer biological half-lives. We hypothesized that increased hydrophobicity allowed interactions with amphiphilic membranes and modulation of biological responses. We find that superwarfarins brodifacoum and difenacoum increase lactate production and cell death in neuroblastoma cells. In contrast, neither causes changes in glioma cells that have higher cholesterol content. After cholet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…These observations are consistent with findings that topical application of warfarin can elicit direct inflammatory responses in skin explants and epithelial cells (Mirkov et al, 2017;Popov Aleksandrov et al, 2015), and that in normal healthy adult mice, treatment with warfarin significantly increased neuroglial activation throughout the brain (Marangoni et al, 2016a). Moreover, X-ray scattering studies show that LAARs such as BDF, but not warfarin, interact with and perturb lipid membrane structures that can result in cellular dysfunction (Marangoni et al, 2016b), including cytotoxicity in diverse cell types (Kalinin et al, 2017;Marangoni et al, 2016b). Together, the data suggest that LAAR exposure which may be insufficient to induce sufficient bleeding and acute death can be causative for increases in inflammatory responses as well as decreases in protective immune responses such as infection and wound healing.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These observations are consistent with findings that topical application of warfarin can elicit direct inflammatory responses in skin explants and epithelial cells (Mirkov et al, 2017;Popov Aleksandrov et al, 2015), and that in normal healthy adult mice, treatment with warfarin significantly increased neuroglial activation throughout the brain (Marangoni et al, 2016a). Moreover, X-ray scattering studies show that LAARs such as BDF, but not warfarin, interact with and perturb lipid membrane structures that can result in cellular dysfunction (Marangoni et al, 2016b), including cytotoxicity in diverse cell types (Kalinin et al, 2017;Marangoni et al, 2016b). Together, the data suggest that LAAR exposure which may be insufficient to induce sufficient bleeding and acute death can be causative for increases in inflammatory responses as well as decreases in protective immune responses such as infection and wound healing.…”
Section: Discussionsupporting
confidence: 86%
“…The observed reductions in core body temperature could therefore reflect initial stages of a systemic inflammatory condition. Alternatively, it has been shown that BDF reduces mitochondrial function (Marangoni et al, 2016b); hence reduced body temperature could be a consequence of reduced energy dissipation during oxidative phosphorylation, which could be exacerbated by lower hematocrit, reduced tissue perfusion and progressive anemia which all contribute to inadequate tissue oxygenation. Consistent with this, it has been reported that certain xenobiotic toxins and some pesticides decrease the metabolic rate of rabbits leading to hypothermia, postulated as a compensatory responses to minimize lethality which in many cases increases with body temperature (Gordon et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These slightly exceeded the densities of 0.304 e -·Å -3 and 0.307-0.311 e -·Å -3 for pure DPPC (51), and dipalmitoyl phosphatidylglycerol (DPPG), respectively (41,52). In turn, the densities of the polar slab 2 ranging within 0.428-0.431 e -·Å -3 (1.26-1.29·ρ aqua ) were lower than those for phospholipids (Table 3) (41,(51)(52)(53)(54). These differences seemed most likely to reflect the presence of cholesterol and the surfactant proteins in CLSE.…”
Section: Effect Of Subphase Clsementioning
confidence: 97%
“…Model lipid monolayers composed of dipalmatidyl phosphatidylcholine (DPPC, a well‐characterized model of biological membranes) in a Langmuir trough can be studied using surface pressure/molecular area isotherms and by X‐ray reflectivity and grazing incidence X‐ray diffraction. Initial studies show that superwarfarins, but not warfarin, can intercalate into DPPC monolayers and cause perturbations in the membrane structure. This is likely due to the extremely high hydrophobic character of the superwarfarins and raises the possibility that membrane disruption contributes to superwarfarin toxicity and tissue damage.…”
Section: Novel Molecular Actions Of Superwarfarinsmentioning
confidence: 99%